(untitled) (LEARNing Landscapes, 2013)
This article documents the rationale and benefits of Forest Schools, while also describing why the organization Forest School Canada was formed. It is based on interviews with two people: Heather Andrachuk, a new teacher in a forest school, and Marlene Powers, a founder of two forest schools and the executive director of Forest School Canada. Narrations from these two women are used to describe the ethos and the pedagogy that results from working within Forest Schools and the origins of Forest School Canada (2013). It also briefly outlines the way Forest Schools serve as an approach to environmental education for early childhood through the development of a sense of attachment to nature.